A Spatial Covariance 1235IA-85380 SPECT Study of α4β2 Nicotinic Receptors in Dementia with Lewy Bodies - Judith Harrison; Sean Colloby; John O’Brien; John Paul Taylor (BJPsych Open, 2025)
Aims: Cholinergic dysfunction is key in dementia with Lewy bodies (DLB), and likely to influence the cognitive and psychiatric symptoms of this condition. However, patterns of spatial covariance in DLB in terms of nicotinic acetylcholine receptors (nAChRs) is unknown. In this study we used 123I-5-iodo-3-[2(S)-2-azetidinylmethoxy] pyridine (1235IA-85380) SPECT (α4β2 nAChR assessment) to investigate the covariance patterns in DLB and their associations with cognition.